1997
DOI: 10.1074/jbc.272.17.11336
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Forms of NOTCH1 Lacking Either the Primary Binding Site for RBP-Jκ or Nuclear Localization Sequences Retain the Ability to Associate with RBP-Jκ and Activate Transcription

Abstract: Truncated forms of the NOTCH1 transmembrane receptor engineered to resemble mutant forms of NOTCH1 found in certain cases of human T cell leukemia/lymphoma (T-ALL) efficiently induce T-ALL when expressed in the bone marrow of mice. Unlike full-sized NOTCH1, two such truncated forms of the protein either lacking a major portion of the extracellular domain (⌬E) or consisting only of the intracellular domain (ICN) were found to activate transcription in cultured cells, presumably through RBP-J response elements w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
182
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(189 citation statements)
references
References 55 publications
(48 reference statements)
7
182
0
Order By: Relevance
“…In most biological assays, the presence of this region has been found to be required to elicit a phenotype Wettstein et al, 1997;Milner et al, 1996), although Notch1 mutants deleted of ankyrin-repeats have been reported to exhibit signi®cant residual activity in some functional assays Aster et al, 1997). Our data also suggest that the ankyrin-repeats are necessary, but not su cient, for transformation of HC11 cells.…”
Section: Structural Requirement Of the Intracytoplasmic Notch1 Proteisupporting
confidence: 52%
See 3 more Smart Citations
“…In most biological assays, the presence of this region has been found to be required to elicit a phenotype Wettstein et al, 1997;Milner et al, 1996), although Notch1 mutants deleted of ankyrin-repeats have been reported to exhibit signi®cant residual activity in some functional assays Aster et al, 1997). Our data also suggest that the ankyrin-repeats are necessary, but not su cient, for transformation of HC11 cells.…”
Section: Structural Requirement Of the Intracytoplasmic Notch1 Proteisupporting
confidence: 52%
“…In addition, these results indicated that the 283 bp region (nt 5270 ± 5553, aa 1734 ± 1821) adjacent to the internal surface of the plasma membrane (domain I) and containing the CBF1/RBP-Jk primary binding site (Aster et al, 1997;Hsieh et al, 1996) and one nuclear localization signal (NLS) is critical for transformation. Our data showed that the ankyrin repeats are not su cient by themselves for transformation since mutant F (DTM) and G (M188) in which the six ankyrin repeats were intact could not induce growth in agar of HC11 cells.…”
Section: Analysis Of the Transforming Potential Of Notch1 Intracytoplmentioning
confidence: 98%
See 2 more Smart Citations
“…The Notch-IC module is characterized by three domains, which have been conserved throughout evolution: (i) the RAM domain adjacent to the transmembrane domain is the major docking site for the RBP-J protein (Jarriault et al, 1995;Tamura et al, 1995;Aster et al, 1997); (ii) the ankyrin repeat domain (ANK) adjacent to the RAM domain mediates further protein-protein interactions (Artavanis-Tsakonas et al, 1999); (iii) the C-terminal domain carries two characteristic features: a polyglutamine region (OPA) and a proline, glutamic acid, serine and threonine rich region termed PEST. Recently, intrinsic transcriptional activation capacity has been assigned to the Notch-IC fragment carrying the OPA motif (Kurooka et al, 1998).…”
Section: Introductionmentioning
confidence: 99%